TEACHERS’ STRATEGIES FOR SHAPING STUDENTS’ LEARNING PERCEPTIONS IN PANDEMIC ERA ONLINE LEARNING - Adela Natassya Ingkafa; Imam Muslih (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2021)
This study aims to analyze teachers’ strategies in shaping students’ learning perceptions during online learning in the pandemic period at MI Bustanul Ulum Brudu Sumobito Jombang. The research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings indicate that teachers implemented adaptive, communicative, and value-based strategies. Online learning was conducted primarily through WhatsApp due to accessibility considerations and students’ socio-economic conditions. Teachers did not merely assign tasks but also provided explanations through voice notes, images, and short videos to maintain students’ understanding and engagement. In addition, teachers reinforced religious values, provided continuous motivation, and established intensive communication with parents. Students’ perceptions of online learning were categorized into positive and negative perceptions, influenced by internal factors such as motivation and learning readiness, as well as external factors including family support and internet connectivity. The study highlights that students’ learning perceptions in online settings are strongly determined by the quality of pedagogical interaction, teachers’ empathy, and their ability to adapt to contextual learning conditions.